2016
DOI: 10.18632/oncotarget.8822
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor RUNX2 regulates receptor tyrosine kinase expression in melanoma

Abstract: Receptor tyrosine kinases-based autocrine loops largely contribute to activate the MAPK and PI3K/AKT pathways in melanoma. However, the molecular mechanisms involved in generating these autocrine loops are still largely unknown. In the present study, we examine the role of the transcription factor RUNX2 in the regulation of receptor tyrosine kinase (RTK) expression in melanoma. We have demonstrated that RUNX2-deficient melanoma cells display a significant decrease in three receptor tyrosine kinases, EGFR, IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
(106 reference statements)
1
24
0
Order By: Relevance
“…Interestingly, RUNX2 physically and functionally interacts with HIF1‐α (Kwon et al., ; Lee et al., ) and RUNX2 stabilizes HIF1‐α under normoxic conditions (Lee et al., ). As mentioned earlier, RUNX2 overexpression in melanoma has been associated with acquired resistance to BRAFi (Anastas et al., ; Boregowda et al., ). Therefore, in addition to increasing RTK expression and promoting migration and invasion (Boregowda et al., ), another mechanism through which RUNX2 might promote resistance would involve HIF‐1α stabilization.…”
Section: Other Transcription Factors Dysregulated During the Process mentioning
confidence: 71%
See 3 more Smart Citations
“…Interestingly, RUNX2 physically and functionally interacts with HIF1‐α (Kwon et al., ; Lee et al., ) and RUNX2 stabilizes HIF1‐α under normoxic conditions (Lee et al., ). As mentioned earlier, RUNX2 overexpression in melanoma has been associated with acquired resistance to BRAFi (Anastas et al., ; Boregowda et al., ). Therefore, in addition to increasing RTK expression and promoting migration and invasion (Boregowda et al., ), another mechanism through which RUNX2 might promote resistance would involve HIF‐1α stabilization.…”
Section: Other Transcription Factors Dysregulated During the Process mentioning
confidence: 71%
“…We previously demonstrated that RUNX2‐deficient melanoma cells displayed a significant decrease in four receptor tyrosine kinases, EGFR, IGF‐1R, PDGFRβ, and AXL, and strongly suggested a role for RUNX2 as a key player in mediating intrinsic RTK‐associated pro‐oncogenic properties in melanoma. In addition, we showed a dramatic upregulation of RUNX2 expression with concomitant upregulation of EGFR, IGF‐1R, and AXL in melanoma cells rendered resistant to PLX4720 (Boregowda et al., ). We then reported that PLX4720‐resistant cells developed in an in vivo context exhibit an increase in RUNX2 levels when re‐exposed to PLX4720 in vitro.…”
Section: Runx2: a New Player In Melanoma Progression And Acquired Resmentioning
confidence: 79%
See 2 more Smart Citations
“…A number of studies have shown that overexpression of AXL in response to therapeutic stress can evolve through a variety of mechanisms, including transcriptional regulation (15,23,24,(50)(51)(52), post-translational regulation (53,54), and expression of miRNA (55) [reviewed in (56) Additionally, blocking AP-1 transcription activity may serve to influence the expression of key RTKs, such as EGFR (62,63), and/or to reduce the expression of the immuno-suppressor modulator of programmed cell death ligand 1 (PD-L1) (64), and hence enhance tumor elimination. The latter possibility is also supported by the findings that AXL and PD-L1 expression are correlated in different cancers (65,66), and in the cancer genome atlas (TCGA) data set for head and neck cancer (data not shown).…”
Section: Discussionmentioning
confidence: 99%